Impact of Inorganic Chemicals on Growth and Yield Potential of Pleurotus sajor-caju - Pal, Sheesh; Biswas, S. K.; Kumar, Ravi; Kumar, Shivam; Kumar, Saurabh; Lal, Kishan; Gautam, Ajay Kumar (International Journal of Bio-resource and Stress Management, 2022)
The experiments on Impact of Inorganic Chemicals on Growth and Yield Potential of Pleurotus sajor-caju were conducted during October–November 2018–2019 and 2019–2020 in Completely Randomized Design at Mushroom Research and Development Centre, Department of Plant Pathology, Chandra Shekhar Azad University of Agriculture and Technology, Kanpur, Uttar Pradesh, India. Among all the treatments, minimum 11 days required for spawn running in the combination of Wheat straw+NPK 5 mg+CaCO3 6 mg. Similarly, the minimum number of days required for pin head formation and harvesting days were also noticed in T5 treatment (wheat straw+5 g NPK+6 g CaCO3), representing 15 and 20 days respectively. The treatment T5 produced maximum number of fruiting bodies where combinations were given as wheat straw+5 g NPK+6 g CaCO3.The maximum stipe length and width of pileus were also recorded maximum in treatment T5, showing 7.9 cm and 13.5 cm against 2.8 cm and 6.6 cm respectively in case of control. Yield potential, total yield and biological efficiency of Pleurotus sajor-caju were also found maximum in treatment T5, representing the values 500, 450, 370, 300 and 250 g yield bag-1 at 1st , 2nd , 3rd, 4th and 5th flushing stages, respectively. On the other hand, the maximum biological efficiency was recorded in T5 (wheat straw+5 g NPK+6 g CaCO3) treatment, showing 37.40 % against 25.68 % in case of treatment T1 (Control). Result showing that treatment T5 (wheat straw+5 g NPK+6 g CaCO3) performed better than all treatments.